The Mineralogical and Chemical Composition of the Strongly Magnetic Egyptian Black Sand Altered Ilmenite - Moustafa, Mohamed Ismail (Engineering, Technology & Applied Science Research, 2023)
The Egyptian black sand contains several types of altered ilmenite grains which have various magnetic susceptibility values, ranging from the strongly paramagnetic, such as ilmenite, to the non-magnetic, such as rutile grains. The altered ilmenite grains of relatively higher mass magnetic susceptibility, separated at 0.1, 0.2, 0.25, and 0.35 A using the Frantz isodynamic magnetic separator, were investigated. Both brown and black altered grains were investigated using the binocular microscope and the Cameca SX-100 microprobe. Most analyzed spots of grains are composed mainly of pseudorutile (psr) and leached pseudorutile (lpsr), with the contents of TiO2 and Fe2O3 ranging between 56.76 and 78.09% and 37.98 and 12.16%, respectively. The Ti/(Ti+Fe) ratio ranges between 0.59 and 0.85. The chemical formula range of the investigated psr-lpsr is Fe2.07-0.54Ti3O9-4.68(OH)0-4.32. The lowest cationic iron content of the lpsr phase is 0.5 with a corresponding molecular formula of Fe0.5Ti3O4.5(OH)4.5. In the detected leached ilmenite spots, the cationic Fe2+ ranges between 0 and 2.46, while the cationic Fe3+ ranges between 0.17 and 1.94. The Ti/(Ti+Fe) ratio ranges between 0.51 and 0.6, and the Fe/Ti ratio ranges between 0.91 and 0.67. Considering the chemical formula of ilmenite is Fe3Ti3O9, the leached ilmenite formulas have the composition Fe2.72-2.02Ti3O9 with the minimum value of total iron being equal to 2.02. Some of the contained inclusions may be responsible for the acquired magnetic characteristics of some of the detected altered grains. The powdered X-ray diffraction patterns of the investigated different magnetic grains were detected before and after heating at 1100 oC for one hour. The hexagonal psr/lpsr structure is more unstable at 1100 oC than the tetragonal rutile structure. According to the calculations of the molecular formulas for the detected alteration phases, the lowest iron content of the altered lpsr is much lower than that previously reported. Also, during the alteration process, the alteration mechanism is changed in the region of 68-70 wt % of contained TiO2. Then, in the late alteration stages, the lpsr structure does not suddenly collapse but gradually produces other associated mineral phases.